Cooperation and conflict in host manipulation: interactions among macro-parasites and micro-organisms - Cézilly, Frank; Perrot-Minnot, Marie-Jeanne; Rigaud, Thierry (Frontiers in Microbiology, 2014)
Several parasite species are known to manipulate the phenotype of their hosts in ways that enhance their own transmission. Co-occurrence of manipulative parasites, belonging to the same species or to more than one species, in a single host has been regularly observed. Little is known, however, on interactions between co-occurring manipulative parasites with same or different transmission routes. Several models addressing this problem have provided predictions on how cooperation and conflict between parasites could emerge from multiple infections. Here, we review the empirical evidence in favor of the existence of synergistic or antagonistic interactions between co-occurring parasites, and highlight the neglected role of micro-organisms. We particularly discuss the actual importance of selective forces shaping the evolution of interactions between manipulative parasites in relation to parasite prevalence in natural populations, efficiency in manipulation, and type of transmission (i.e., horizontal versus vertical), and we emphasize the potential for future research.